Micro-RBS study of nickel silicide formation - Lee, Pooi See (2013)
Two MeV He+ microbeam-Rutherford backscattering (μ-RBS) is used to obtain information on silicide formation in patterned nickel silicide samples under different annealing conditions. It is important to characterize silicide formation processes in such laterally non-homogenous samples in order to understand resistivity variations that are observed when metal oxide silicon field effect transistor (MOSFET) gate lengths are reduced, and when silicidation temperatures are changed. The patterned samples investigated consist of an array of square pads (View the MathML source) of the structure Ni(Pt)Six/Poly-Si (2000 Å)/SiO2 (2500 Å)/Si and narrow lines of 100 μm length and linewidths of 5 and 2 μm. μ-RBS (∼View the MathML source beam spot) was used to obtain the thickness and stoichiometry of the silicide films for the square pads. The beam was focused to submicron dimensions for the scans over the narrow lines. μ-RBS results for the different silicide structures are presented and correlated with micro-Raman data.